WORK SIMPLIFICATION FOR PRODUCTIVITY IMPROVEMENT A case study: Kaliti Metal Products Factory - Kitaw, Daniel (Zede Journal of Ethiopian Engineers and Architects, 2023)
The tools and techniques of work simplification are used increasingly in industries, utilities, private and government institutions, and in all process involving tasks including paper works. Articles in the popular press concerning the work simplification techniques state that Productivity shall improve upon intelligently developed and improved work methodsby elimination of waste of any kind in a process. This article introduces the tools and techniques of work simplification, implementation strategies for productivity improvement and its application in Kaliti Metal Products Factory. The outcome of the research has indicated an encouraging result. The probable annual net profit gain by use of the simplified work method developed, as applied to tube production only, is estimated to be Birr 3 million. This profit gain would have increased the 1993 E. C. declared profit by over 55% Application of the same principles for other types of production, Secco profile, Cut-to-size plates, etc., is likely to generate more profit gain.